Local oxophilicity Sm incorporation drives structural alteration of Cu2O/Cu catalyst in CO2 electroreduction - Zihao Wei; Yulin Qin; Mengbo Zou; Lin Jia; Haorun Li; Yuekun Zhang; Jinyu Wang; Zeyu Guo; Hao Wu; Zeyu Zhang; Shanghong Zeng (Journal of Environmental Chemical Engineering, 2026)

Multilayer packaging with CO2/O2-selective gas regulation and humidity-responsive release of cinnamon essential oil for cherry tomato preservation - Lin Peng; Jinyu Wang; Lijing Lin; Azadeh Nilghaz; Xueyan Yun; Xiaofang Wan; Shaokai Zhang; Junfei Tian (Food Chemistry, 2026)

Neural stem cell extracellular vesicle-mediated delivery of astragaloside IV attenuates hypoxic-ischemic brain damage by activating the mTOR pathway - Ruiqin Yu; Huizhong Bai; Yanjun Mo; Gang Liu; Zhuoluo Zhou; Lin Xu; Bowen Deng; Xiaoye Li; Jinyu Li; Houjun Zhang; Xiaohong Mu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Sensitivity of urban green space disparity assessment to NDVI data sources, acquisition timing, and alternative metrics - Jinyu Kong; Yang Ju; Iryna Dronova; Ying Liang; Jian Lin; Qin Ma (Urban Forestry & Urban Greening, 2026)

Ginsenoside Rb1 attenuates hyperoxia-induced lung injury in neonatal rats by inhibiting ferroptosis via the system Xc− pathway - Huidan Lian; Haiyu Zhou; Jie Dong; Junyi Qian; Yue Cheng; Jinyu Lou; Xinqi Zheng; Wei Lin; Danyun Jia (Toxicology and Applied Pharmacology, 2026)

Pt(II) complexes with narrow-spectrum emission for high-performance green organic light-emitting diodes - Qinghua Xia; Yong Cao; Yihan Chu; Yang Li; Xuanbo Hu; Jinyu Song; Cong Zhang; Xiao-Chun Hang; Lin Xu (Chemical Engineering Journal, 2026)

A wearable sonodynamic therapy platform with a piezocatalytic nanocomposite hydrogel for diabetic wound healing - Jinyu Lin; Moxu Wang; Hongchao Li; Yuxin Wang; Jie Xu; Xiandi Jin; Xiaoming Lou; Tao Liu; Zhixuan Liu; Wenwu Cao; Hua Yuan; Xiaohua Jian (Chemical Engineering Journal, 2026)

DynamicDTA: Drug-Target Binding Affinity Prediction Using Dynamic Descriptors and Graph Representation - Dan Luo; Jinyu Zhou; Le Xu; Sisi Yuan; Xuan Lin (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Identification and Characterization of Flavobacterium psychrophilum as a Causative Pathogen in Farmed Grass Carp Ctenopharyngodon idella in China - Jiahao Li; Lingyun Lin; Jinyu Shen; Jiayun Yao; Xiao Liu; Xiaoyi Pan (Journal of Fish Diseases, 2026)
In March 2024, a severe mass mortality event occurred at a grass carp ( Ctenopharyngodon idella ) farm in Zhejiang, China, resulting in a cumulative mortality rate of 70%. To identify the causative agent, 12 bacterial isolates that exhibited the same phenotypic characteristics were isolated from diseased fish. A further phylogenetic (16S rDNA) characterization identified the bacterium as Flavobacterium psychrophilum . Genetic characterization revealed that all 12 bacterial isolates belonged to serotype Type‐1 and sequence type ST418, a newly documented ST closely associated with cyprinid fish hosts. In infection trials, the bacterium exhibited clear virulence in grass carp, producing clinical signs consistent with those observed during the outbreak. Furthermore, histopathology of diseased fish with F. psychrophilum revealed ulcerative dermatitis with associated myositis, proliferative branchitis, vascular congestion and focal necrosis in the liver, multifocal necrosis in the spleen, and tubular dilation with renal corpuscle necrosis in the kidney. Given the potential risk of cross‐species transmission among cyprinid fish, we also evaluated the pathogenicity of this bacterium in Prussian carp ( Carassius gibelio ), a widely cultured species in China. To our knowledge, this study represents the first report of F. psychrophilum causing mass mortality in farmed grass carp in China and provides essential information to support improved prevention and risk mitigation strategies for this emerging disease.

Faulting structure and seismic hazard: Insights from the 2024 MW 5.2 Bakersfield earthquake sequence - Weidong Li; Pengcheng Zhou; Fan Zhang; Jiangyang Zhang; Zhiyuan Zhou; Tao Zhang; Jinyu Tian; Jian Lin (Tectonophysics, 2026)

Origin, evolution and precipitation mechanism of ore-forming fluids in Jiaojia belt, Jiaodong Peninsula: Insights from trace elements and S Fe isotopes of pyrite - Jinyu Cheng; Lin Yang; Qingfei Wang; Yixin Li; Wen Zhang; Bin Sun; Xue Dong; Shiyu Zhao; Dapeng Li; Kexin Zhao; Hong Wang (Journal of Geochemical Exploration, 2026)

CBC3T-3: a novel patient-derived cisplatin-resistant distal cholangiocarcinoma cell line harboring multiple TP53 missense mutations - Jiahui Xi; Mingzhen Bai; Ruyang Zhong; Chongfei Huang; Ruoshui An; Long Gao; Haidong Ma; Liang Tian; Jinyu Zhao; Ningzu Jiang; Xiang He; Leiqing Wang; et al. (Human Cell, 2026)
Distal cholangiocarcinoma (dCCA) is a malignant tumor characterized by a challenging diagnosis, high invasiveness, and extremely poor prognosis. Research on dCCA is limited by the scarcity of reliable patient-derived preclinical tumor models. This study established a novel human distal cholangiocarcinoma cell line, CBC3T-3, and systematically characterized its biological properties, genomic features, and potential for clinical application. This cell line was extracted from postoperative distal cholangiocarcinoma tumor from a 54-year-old male patient. It was stably passaged (> 50 generations) through primary culture and condition optimization, preserving the same pathology as that of the primary tumor. Whole-exome sequencing (WES) confirmed somatic mutations, tumor mutation burden, single-sample clonal structure, driver genes, and drug resistance genes in CBC3T-3 cells, revealing their genomic characteristics. Functional assays demonstrated that CBC3T-3 cells exhibit strong capabilities for proliferation, migration, and invasion in vitro. In a subcutaneous xenograft model in immunodeficient mice, palpable tumor nodules developed within 4 weeks, reflecting the clinical characteristics of rapidly progressive disease. Drug sensitivity analysis revealed that, compared with TFK-1 cells, CBC3T-3 cells presented significantly greater responses to paclitaxel, gemcitabine, and oxaliplatin but relatively poor responses to 5-FU and cisplatin. The integration of drug resistance gene findings from WES suggests that TP53 missense mutations may mediate primary resistance to cisplatin. The establishment of the CBC3T-3 cell line enhances the research toolkit for dCCA. Its genomic characteristics and functional plasticity provide a reliable preclinical tumor model for developing precision therapies and investigating drug resistance mechanisms.

Establishment of a spinal cord-derived cell line from Micropterus salmoides reveals differential host-pathogen interactions and innate immune evasion strategies - Xin Chu; Lingyun Lin; Jinpeng Gong; Mingyue Gao; Jinyu Shen; Yan Zhang; Xiaoyi Pan (Aquaculture, 2026)

Electrophysiological Characterization of Murine Vestibular Efferent Neurons and Modulation by Acute Peripheral Vestibular Deprivation - Jinyu Wang; Mengfan Xu; Lei Zhang; Wenjie Liu; Siyue Wang; Liqin Wang; Ning Cong; Geng-Lin Li; Jing Wang (Neuroscience Bulletin, 2026)
Vestibular efferent neurons in the brainstem provide direct cholinergic innervation to peripheral vestibular organs, thereby modulating their sensory responsiveness. In this study, a genetically targeted mouse model with choline acetyltransferase-driven fluorescent labeling enabled the precise localization of these neurons to the dorsolateral region of the genu of the facial nerve. Whole-cell patch-clamp recordings in acute brainstem slices revealed that virtually all neurons exhibited spontaneous action potential firing, with marked heterogeneity in discharge patterns and after-hyperpolarization kinetics. Prominent A-type potassium currents were identified and found to be differentially regulated by acetylcholine and calcitonin gene-related peptide. Acute unilateral vestibular deprivation induced a bilateral enhancement of spontaneous firing, indicating sensitivity to altered sensory input. These findings define the intrinsic electrophysiological properties and neuromodulatory mechanisms of vestibular efferent neurons, providing mechanistic insight into their roles in both physiological regulation and adaptive plasticity within the vestibular system.

Ecological land as a sink: spatial spillover effects and synergistic governance of PM2.5-O3 co-pollution in Coastal China - Jinyu Liu; Mengjie Guo; Qiaoya Lin; Shurui Chen; Zhenzhen Cao; Wei Shui; Cong Jiang (Environmental Monitoring and Assessment, 2026)

Overview of strategies for 3D printing of fruit and vegetables: Mechanism, modification, challenges and future trends - Baoguo Xu; Bingbing Mao; Xiaodie Wang; Jinyu Liu; Zhenbin Liu; Chaofan Guo; Benxi Wei; Lin Lin; Zhimei Guo; Min Zhang; Cunshan Zhou; Haile Ma (Food Research International, 2026)

Chitosan-SNAP composite coating with sustained NO release for microbial killing and tomato preservation - Jie Chen; Hui Zhang; Yuxin Lin; Jinyu Liu; Yisong Chen; Xiaoyan Zhang; Hetong Lin; Da-Peng Yang (Food Chemistry, 2026)

The p -JNKThr183/Tyr185 / p -Keap1Thr43 /Keap1 axis mediates arsenic-induced endothelial dysfunction by coordinating Chaperone-mediated autophagy with macroautophagy - Jinyu Li; Jin Cheng; Zhihan Yang; Lin Gao; Qiaoling Liu; Jing He; Yishan Dong; Shuo Wang; Jing Cui; Ziqi Xu; Dianjun Sun; Wei Zhang (Chemico-Biological Interactions, 2026)

Esculin Alleviated NLRP3 Inflammasome Activation by Inducing PINK1/Parkin-Mediated Mitophagy in Cerebral Ischemia–Reperfusion Injury - Jinyu Lin; Bowen You; Xin Yang; Xue Li; Wenjuan Sun; Zhongyu Xu; Yi Zhang; Xuhui Tong; Shuying Dong (Molecular Neurobiology, 2026)

Examinations of Surface Waves and Ocean Circulation During Severe Weather Conditions over the Northwest Atlantic Using a Coupled Wave–Current Modelling System: An Overview - Jinyu Sheng; Qiantong Pei; Shangfei Lin; Colin Hughes (Journal of Marine Science and Engineering, 2025)
Upper oceans are highly energetic during a severe weather event, with large surface waves and intense ocean currents over areas affected by the storm. An advanced and coupled wave–current modelling system for the northwestern Atlantic (WCMS-NWA) was developed by the Regional Modelling Group at Dalhousie University for simulating surface waves and three-dimensional ocean currents over the eastern Canadian shelf and adjacent waters. Applications of this modelling system during different weather events have been discussed separately in the past. In this overview, the model performances of WCMS-NWA and major hydrodynamics over the study region during 11 severe storms are summarized. Comparisons of model results with in situ oceanographic observations and satellite data demonstrate the suitability and accuracy of WCMS-NWA in simulating ocean circulation and surface waves during normal weather conditions and intense ocean currents and extreme surface waves during severe storm events. It is shown that satisfactory model performance of WCMS-NWA requires reliable temporal–spatial representations of atmospheric forcing and inclusions of interactions between waves and currents (WCIs). Important contributions from WCIs during these severe weather conditions are discussed based on the model results.

A pre-training enhanced deep learning framework for robust sparse unmixing in chemical imaging - Yue Wang; Anqi Liu; Lin Tan; Jinyu Sun; Hailiang Zhang; Ting Xie; Zhimin Zhang; Hongmei Lu (Analytica Chimica Acta, 2025)

Novel thin film nanocomposite membranes developed via polydopamine nanoparticles, Halloysite nanotubes and Cu-MOF nanosheets for dye removal - Junfeng Zheng; Jinyu Liu; Zikang Qin; Yulei Ma; Yahui Yang; Linlin Yang; Hang He; Zhongde Dai; Wenju Jiang; Lin Yang; Lu Yao; Bo Tang (Journal of Environmental Chemical Engineering, 2025)

Correction: Three new species from the Middle Jurassic of China provide insights on wing spots diversity of Bittacidae (Insecta: Mecoptera) - Jiamiao Yu; Jinyu Wang; Yanjie Zhang; Chungkun Shih; Dong Ren; Xiaodan Lin; Hongru Yang (The Science of Nature, 2025)

Transient receptor potential vanilloid-1 (TRPV1) is a mediator of noise-induced neural damage in zebrafish and mice - Ruicun Liu; Boyu Luo; Honglu Yan; Qing Lin; Wei Liu; Xiaowei Hao; Shuai Huang; Zhenjun Luo; Tuoyu Liu; Jinyu Li; Zhiyuan Shi; Songzuo Liu; et al. (Science China Life Sciences, 2025)

Three new species from the Middle Jurassic of China provide insights on wing spots diversity of Bittacidae (Insecta: Mecoptera) - Jiamiao Yu; Jinyu Wang; Yanjie Zhang; Chungkun Shih; Dong Ren; Xiaodan Lin; Hongru Yang (The Science of Nature, 2025)

Temporal Dynamics of Immune Response Signalling in Largemouth Bass ( Micropterus salmoides ) Infected With Largemouth Bass Virus - Xin Chu; Jing Chen; Lingyun Lin; Jiayun Yao; Lei Huang; Mingyue Gao; Jinyu Shen; Xiaoyi Pan (Journal of Fish Diseases, 2025)
The largemouth bass virus (LMBV) significantly impacts Chinese largemouth bass aquaculture. The molecular mechanisms regulating LMBV virulence and the gene responses stimulated in the host during infection remain unclear. This study investigates the transcriptional dynamics and signalling pathways activated during the immune response to LMBV by analysing the transcriptome of head kidney tissues at 1, 4, 7, and 28 days post‐infection (dpi) using RNA sequencing. Histopathological and viral load analyses indicated early tissue disruption, followed by extensive recovery by 28 dpi. Analysis of differentially expressed genes (DEGs) and weighted gene co‐expression network analysis (WGCNA), combined with Venn analysis of samples at 1, 4, and 7 dpi, identified significant and common genes. Early infection triggered robust innate immunity through activation of the RIG‐I like receptor and cGAS‐STING signalling pathways, which activated type I interferons (IFNs) and interferon‐stimulated genes (ISGs). Later stages indicated activation of adaptive immune responses. Validation of randomly selected genes via RT‐qPCR confirmed the RNA‐seq results, showing consistent expression patterns. This comprehensive study offers new insights into the sustained innate and adaptive immune responses to LMBV.

The independent and combined associations of nocturnal sleep duration, sleep midpoint, and sleep onset latency with global cognitive function in older Chinese adults - Xueyao Wu; Jiaqiang Liao; Xin Chen; Jinyu Xiao; Xinyang Dui; Tianpei Ma; Lin Hu; Xunying Zhao; Qian Bu; Mengyu Fan; Tao Zhang; Lu Long; et al. (GeroScience, 2025)

Study on the pathways of thermochemical sulfate reduction between sulfates and alkanes at low temperatures - Yiya Wang; Liqiang Zhang; Chuantao Zhu; Riyi Lin; Xinlu Han; Kunlun Xie; Ruiqi Liu; Jinyu Li; Chenxing Huang; Qiwei Dong; Xinwei Wang (Fuel, 2025)

Phase-separated anisotropic PVA hydrogel loaded with tetramethylpyrazine for spinal cord injury repair - Gang Liu; Shenglin Li; Bowen Deng; Luyao Huo; Huizhong Bai; Shengyuan Jiang; Yimin Zhou; Zhenzhen Pei; Ceren Kimna; Yi Zhao; Lin Xu; Jinyu Li; et al. (Chemical Engineering Journal, 2025)

LCN2 Regulates Microglia Polarization Through the p38MAPK-PGC-1α-PPARγ Pathway to Alleviate Traumatic Brain Injury - Hanjian Du; Jun Lai; Bo Lin; Jinyu Pan; Yanghao Zhou; Yimo Feng (Cell Biochemistry and Biophysics, 2024)

A smart home energy management system based on human activity recognition and deep reinforcement learning - Zhouwen Wu; Xia Chen; Yujun Lin; Jinyu Wen; Yin Chen (Energy and Buildings, 2024)

Convergence and divergence of storm waves induced by multi-scale currents: Observations and coupled wave-current modeling - Shangfei Lin; Jinyu Sheng; Jinhai Zheng; Aifeng Tao (Coastal Engineering, 2024)

Virtual Reality Fusion Testing-Based Autonomous Collision Avoidance of Ships in Open Water: Methods and Practices - Haiming Zhou; Mao Zheng; Xiumin Chu; Chengqiang Yu; Jinyu Lei; Bowen Lin; Kehao Zhang; Wubin Hua (Journal of Marine Science and Engineering, 2024)
With the rapid development of autonomous collision avoidance algorithms on ships, the technical demand for the testing and verification of autonomous collision avoidance algorithms is increasing; however, the current testing of autonomous collision avoidance algorithms is mainly based on the virtual simulation of the computer. To realize the testing and verification of the autonomous collision avoidance algorithm in the real ship scene, a method of virtual reality fusion testing in open water is proposed and real ship testing is carried out. Firstly, an autonomous ship collision avoidance test and evaluation system is established to research the test method of ship encounters in open water. Starting from the convention on the international regulations for preventing collisions at sea (COLREG), the main scenario elements of ship collision avoidance are analyzed. Based on the parametric modeling method of ship collision avoidance scenarios, a standard test scenario library for ship collision avoidance in open waters is established. Then, based on the demand for a ship collision avoidance function test, the evaluation index system of ship collision avoidance is constructed. Subsequently, for the uncertainty of the initial state of the real ship test at sea, the virtual–real space mapping method to realize the correspondence of the standard scenario in the real world is proposed. A standardized testing process to improve testing efficiency is established. Finally, the method of conducting virtual simulation and virtual reality fusion tests for various scenarios are verified, respectively. The test results show that the test method can effectively support the testing of autonomous collision avoidance algorithms for ships in open waters and provide a practical basis for improving the pertinence and practicability of ship collision avoidance testing.

A conical spiral methanol steam reforming reactor for spectral splitting-based concentrating photovoltaic-thermochemical hybrid production - Riyi Lin; Jinyu Li; Yi Ge; Yiya Wang; Pengyu Chen; Huanan Li; Qiwei Dong; Ruiqi Liu; Chenxing Huang; Xinwei Wang; Zhengda Yang (Journal of Cleaner Production, 2024)

Efficient capture of CO2 from flue gas and biogas by moisture-stable adenine-based ultramicroporous metal-organic framework - Fang Shen; Jinyu Wu; Guanyu Chen; Zongwu Wei; Jiayi Wang; Zhiqiang Lin; Kungang Chai (Journal of Environmental Chemical Engineering, 2024)

Organophosphate esters (OPEs) pollution characteristics, bioaccumulation and human consumption implication in wild marine organisms from the Yellow River Estuary, China - Jianing Lin; Xinshu Ding; Jinzeng Gu; Lutao Zhang; Jinyu Chao; Heng Zhang; Song Feng; Changsheng Guo; Jian Xu; Zhenhui Gao (Marine Pollution Bulletin, 2024)

Enhanced vanadium bioleaching from stone coal employing Aspergillus niger: Optimization of stone coal pretreatment method - Yingbo Dong; Jinyu Zan; Hai Lin (Minerals Engineering, 2024)

Co-exposure of polystyrene nanoplastics and copper induces development toxicity and intestinal mitochondrial dysfunction in vivo and in vitro - Jinyu Rong; Chenwei Yuan; Xiang Yin; Xiaohan Wu; Fei He; Yixin Wang; Kelvin Sze-Yin Leung; Sijie Lin (Science of The Total Environment, 2024)

Ranking the risk of antibiotic resistance genes by metagenomic and multifactorial analysis in hospital wastewater systems - Xinyi Shuai; Zhenchao Zhou; Lin Zhu; Chioma Achi; Zejun Lin; Zhe Liu; Xi Yu; Jinyu Zhou; Yanhan Lin; Hong Chen (Journal of Hazardous Materials, 2024)

Establishing a pulmonary aspergillus fumigatus infection diagnostic platform based on RPA-CRISPR-Cas12a - Chunhui Lin; Jing Zhou; Nana Gao; Runde Liu; Ge Li; Jinyu Wang; Guoping Lu; Jilu Shen (World Journal of Microbiology and Biotechnology, 2024)

ZrO2-MoO3/modified lotus stem biochar catalysts for catalytic aquathermolysis of heavy oil at low-temperature - Yiya Wang; Riyi Lin; Liqiang Zhang; Xinlu Han; Jinyu Li; Chenxing Huang; Qiwei Dong; Pengyu Chen; Huanan Li; Xinwei Wang (Fuel, 2024)

Effects of gas to water ratio and nano-Cu dosage on CH4 hydrate growth: A combined molecular simulation and experimental study - Chenxing Huang; Riyi Lin; Chang Lu; Xichong Yu; Zhengda Yang; Chengzhi Wu; Jinyu Li; Yiya Wang (Fuel, 2024)

Association of systemic inflammation with the obesity paradox in cancer: results from multi-cohort studies - Hailun Xie; Lishuang Wei; Heyang Zhang; Guotian Ruan; Xiaoyue Liu; Shiqi Lin; Jinyu Shi; Chenan Liu; Xin Zheng; Yue Chen; Hanping Shi (Inflammation Research, 2024)

Bacteriophages: Vectors of or weapons against the transmission of antibiotic resistance genes in hospital wastewater systems? - Xinyi Shuai; Zhenchao Zhou; Xiaoliang Ba; Yanhan Lin; Zejun Lin; Zhe Liu; Xi Yu; Jinyu Zhou; Guangshu Zeng; Ziye Ge; Hong Chen (Water Research, 2024)

AMPKα is active in autophagy of endothelial cells in arsenic-induced vascular endothelial dysfunction by regulating mTORC1/p70S6K/ULK1 - Ziqi Xu; Qiaoling Liu; Jinyu Li; Jingqiu Wang; Zhihan Yang; Juan Wang; Lin Gao; Jin Cheng; Jing He; Yishan Dong; Xiangnan Guo; Jing Cui; et al. (Chemico-Biological Interactions, 2024)

Effects of Inorganic Arsenic on Type 2 Diabetes Mellitus In Vivo: the Roles and Mechanisms of miRNAs - Jackson Sira; Xiaodan Zhang; Lin Gao; Therese Martin Cheteu Wabo; Jinyu Li; Caselia Akiti; Wei Zhang; Dianjun Sun (Biological Trace Element Research, 2024)

Recovery of precious metals from waste printed circuit boards though bioleaching route: A review of the recent progress and perspective - Yingbo Dong; Nuo mingtana; Jinyu Zan; Hai Lin (Journal of Environmental Management, 2023)

Bioleaching of heavy metals from metal tailings utilizing bacteria and fungi: Mechanisms, strengthen measures, and development prospect - Yingbo Dong; Jinyu Zan; Hai Lin (Journal of Environmental Management, 2023)

Developing a novel Gaussian process model predictive controller to improve the energy efficiency and tracking accuracy of the pressure servo control system - Zhonglin Lin; Jinyu Gan; Qiang Qian; Feng Huang; Xinglong Zhang; Tianhong Zhang; Wenchao Liu (Journal of Cleaner Production, 2023)

Rapid and effective detection of Macrobrachium rosenbergii nodavirus using a combination of nucleic acid sequence-based amplification test and immunochromatographic strip - Feng Lin; Jinyu Shen; Yuelin Liu; Aixia Huang; Haiqi Zhang; Fan Chen; Dongren Zhou; Yang Zhou; Guijie Hao (Journal of Invertebrate Pathology, 2023)

Enhanced bioleaching efficiency of vanadium from stone coal vanadium ore by adding biochar and plasma treatment - Yingbo Dong; Jinyu Zan; Hai Lin (Minerals Engineering, 2023)

Time to reconsider the enigmatic tail of eastern Paleo-Tethys: New insights from Borneo - Xiao Ran Zhang; Sun-Lin Chung; Azman A. Ghani; Rezal Rahmat; Yi-Ju Hsin; Hao-Yang Lee; Ping-Ping Liu; Jinyu Xi (Lithos, 2023)

Interactions between Surface Waves, Tides, and Storm-Induced Currents over Shelf Waters of the Northwest Atlantic - Shangfei Lin; Jinyu Sheng (Journal of Marine Science and Engineering, 2023)
A coupled wave–tide–circulation model is used to investigate wave–current interactions (WCIs) over the shelf waters of the Northwest Atlantic (NWA) during Hurricane Earl (2010). WCIs have substantial impacts on hydrodynamics in the upper ocean. The significant wave heights are modulated by WCIs, particularly over regions with strong current gradients, with a reduction up to ~2.1 m (20%) during the storm. Noticeable decreases in surface elevations and tidal currents occur in regions with strong tides such as the Gulf of Maine, mainly due to the wave-enhanced bottom stress. Over regions with weak tidal currents, wave effects on currents are dominated by two competitive processes between wave-induced forces and wave-enhanced mixing. The former strengthens surface currents (up to ~0.55 m/s) and increases the peak storm surge (up to ~0.48 m). The latter is responsible for the reduction in storm-induced surface currents (up to ~0.94 m/s) and anticyclonic modulation of current directions. Vertically, WCIs extend the strong vertical current shear and shift it downward during the storm, which enhances the local mixing and changes the structures of near-inertial oscillations (NIOs). Moreover, tidal currents also change the magnitudes of the NIOs and subtidal currents and affect the intensity of WCIs.

Pollution characteristics and risk assessment of organophosphate esters in aquaculture farms and natural water bodies adjacent to the Huanghe River delta - Jinyu Chao; Song Feng; Yingdong Hao; Jianing Lin; Bin Zhang (Journal of Oceanology and Limnology, 2023)

Establishment and characterization of a spinal cord tissue cell line from mandarin fish, Siniperca chuatsi and its susceptibility to several viruses - Jinpeng Gong; Xiaoyi Pan; Lingyun Lin; Yue Zhu; Jiayun Yao; Congxu Wang; Wenlin Yin; Lei Huang; Yihan Liu; Fan Chen; Jinyu Shen (Journal of Fish Diseases, 2022)
In this study, we established and characterized a continuous cell line from the spinal cord tissue of mandarin fish, Siniperca chuatsi and assessed its susceptibility to infectious spleen and kidney necrosis virus (ISKNV), Siniperca chuatsi ranavirus (SCRaV) and Siniperca chuatsi rhabdovirus (SCRV). The cell line, named SCC, has been successively cultured up to 40 passages. The optimal growing conditions of SCC cells were in Leibovitz's L‐15 medium supplemented with 20% foetal bovine serum (FBS) at 28°C. Karyotype analysis demonstrated 48 normal diploid chromosomes in the cells. The identity of S. chuatsi origin of SCC cells was confirmed by partial sequencing of the 16S rRNA and cytochrome oxidase I ( COI ) genes. Infection susceptibility assessment showed that ISKNV, SCRIV and SCRV and can be stably produced and transmitted in SCC cells, and the replication efficiency of ISKNV, SCRaV and SCRV ranged from 10 7.4 to 10 9.6 TCID 50 /ml. In addition, transmission electron microscopy analysis of ISKNV, SCRAV and SCRV infected SCC cells showed numerous viral particles. In conclusion, the newly established SCC cells provide an important tool for isolation and production of viruses, as well as for molecular and cell biology studies.

TMEM166 inhibits cell proliferation, migration and invasion in hepatocellular carcinoma via upregulating TP53 - Jiejie Yang; Bin Wang; Qian Xu; Yuling Yang; Lin Hou; Kan Yin; Qingming Guo; Yanan Hua; Li Zhang; Yixuan Li; Jinyu Zhang; Ning Li (Molecular and Cellular Biochemistry, 2021)

Hazard analysis of typhoon disaster-causing factors based on different landing paths: a case study of Fujian Province, China - Jinyu Ye; Guangfa Lin; Minfeng Zhang; Lu Gao (Natural Hazards, 2020)

Identification of De Novo DNMT3A Mutations That Cause West Syndrome by Using Whole-Exome Sequencing - Zhenwei Liu; Zhongshan Li; Xiao Zhi; Yaoqiang Du; Zhongdong Lin; Jinyu Wu (Molecular Neurobiology, 2018)

Exogenous spermidine alleviates fruit granulation in a Citrus cultivar (Huangguogan) through the antioxidant pathway - Bo Xiong; Shuang Ye; Xia Qiu; Ling Liao; Guochao Sun; Jinyu Luo; Lin Dai; Yi Rong; Zhihui Wang (Acta Physiologiae Plantarum, 2017)

Changes in local oceanographic and atmospheric conditions shortly after the 2004 Indian Ocean tsunami - Zhongzhen Yan; Yi Sui; Jinyu Sheng; Danling Tang; I-I Lin (Ocean Dynamics, 2015)

A numerical study of the circulation and monthly-to-seasonal variability in the Caribbean Sea: the role of Caribbean eddies - Yuehua Lin; Jinyu Sheng; Richard J. Greatbatch (Ocean Dynamics, 2012)

The influence of Gulf of Mexico Loop Current intrusion on the transport of the Florida Current - Yuehua Lin; Richard J. Greatbatch; Jinyu Sheng (Ocean Dynamics, 2010)